درجة توافر الكفايات الرقمية لدى معلمي التعليم الأساسي في ضوء معايير الجمعية الدولية للتكنولوجيا في التعليم ISTE (دراسة ميدانية في مدينة طرطوس) (Journal of Hama University, 2024)
The research aimed to identify the degree of availability of digital competencies among basic education teachers in the city of Tartous in light of the standards of the International Society for Technology in Education ISTE. The research sample consisted of (326) male and female basic education teachers in the city of Tartous, according to the research variables (academic qualification, Teaching experience), and to achieve the goal of the research, reliance was placed on the descriptive analytical approach, and a questionnaire consisting of (28) items was used, which included seven dimensions (learning teacher, leader, citizen, collaborator, designer, facilitator, analyst) prepared by the researcher, after Its validity and reliability were verified, and the results were as follows:- The degree of availability of digital competencies among basic education teachers in the city of Tartous in light of the standards of the International Society for Technology in Education (ISTE) is average, with an arithmetic mean (2.99) and a standard deviation (0.536).- There are statistically significant differences between the average scores of the research sample members on the digital competencies questionnaire according to the academic qualification variable, and in favor of postgraduate studies.- There are no statistically significant differences between the average scores of the research sample members on the digital competencies questionnaire according to the teaching experience variable.In light of the results obtained, the current research suggested the need to pay attention to applying the standards of the International Society for Educational Technology (ISTE) and employing them in the educational process by providing intensive training courses, workshops, and seminars to improve teachers’ professional competencies.